Carbocyclic pincer carbene complexes of ruthenium: syntheses and reversible hydrogenation. Issue 34 (9th August 2021) - Wiedmaier, Nicholas R.; Schubert, Hartmut; Mayer, Hermann A.; Wesemann, Lars
Abstract : Double C–H activation leads to the formation of a ruthenium carbocyclic carbene PCP pincer complex. Uptake and release of three equivalents of hydrogen involving the cycloheptatriene moiety acting as a cooperative ligand was realized. Abstract : The ruthenium carbene pincer complex 2 was synthesized treating the benzo annulated cycloheptatriene bisphosphine 1 with RuCl3 . Addition of three equivalents of hydrogen to the carbocyclic carbene complex 2 was achieved in reaction of 2 with hydrogen at elevated temperatures. Hydrogenated complex 4, exhibiting a rigid chair conformation in solution, was dehydrogenated by heating a toluene solution of complex 4 to reflux for 5–7 d. In reaction with ethylene, complex 4 transfers one equivalent of hydrogen, forming ethane and alkyl complex 5 .